TASDOKU-BA - Fkhururazi, Siti Nurmaisarah; Nadhirah, Farhah; Mohamad, Madiha Fatin; Fkhururazi, Siti Nurmaimanah; Ali, Alizah; Uteh, Nor Fazlin; Mohammed Zabidi, Mahfuzah (Multidisciplinary Applied Research and Innovation, 2022)
Arabic is now gaining popularity in the Malaysian education arena. However, most students face problems while learning this language. In addition, there are some students who fail to remember the change of verbs (tasrif fiil) in Arabic which becomes the cause of difficulty for students to master learning and thus has negative implications for Arabic communication in verbal or writing. Thus, this innovation is intended as a teaching materials in remembering tasrif fiil madhi. TASDOKU-BA is a processed and inspired from the number-based sudoku game. The method used is also relaxed and attracts students’ attention, which is in the form of a game with the goal to bring enjoyment to students learning Arabic as well as help the process of remembering tasrif well. TASDOKU-BA is innovated to 14 changes according to the change of Arabic verbs that have passed (tasrif fiil madhi). Each empty column of TASDOKU-BA must be filled with a different and non-repeating tasrif fiil madhi. Indirectly, the students repeated the tasrif fiil madhi as many as twenty-eight times during the session to find the correct tasrif fiil madhi. Fifteen groups were formed which consist of current students taking on the subject of Arabic Language at Johor Branch Pasir Gudang Campus. A positive results when almost all groups are able to fill in the answers to all TASDOKU-BA blank columns within 35 minutes. Thus, this TASDUKO-BA game is very suitable for students at all level of learning, regardless of university, high school, and even students in primary school can also play this game to master themselves in the tasrif fiil madhi verbs. It is also beneficial to teachers and lecturers in finding interactive and effective learning methods more effectively.